Síndrome torácico agudo en pacientes con anemia de células falciformes. - ECKARDT, Paula (2013)
We report an unusual lethal complication of sickle cell anemia. The patient was admitted with a diagnosis of acute chest syndrome and died shortly thereafter of respiratory failure. Autopsy revealed numerous deposits of bone marrow hematopoietic tissue occluding the microvascular circulation of the lung. Numerous causes of acute chest syndrome in sickle cell anemia have been identified, including pulmonary embolism from infartion of bone marrow. However, the release of bone marrow hematopoietic tissue leading to pulmonary vascular occlusion is not generally recognized pre-mortem by treating physicians.